Crystal engineering of a zwitterionic drug to neutral cocrystals: a general solution for floxacins - Gunnam, Anilkumar; Suresh, Kuthuru; Ganduri, Ramesh; Nangia, Ashwini (Chemical Communications, 2016)
The transformation of zwitterionic Sparfloxacin (SPX) to the neutral form is achieved by cocrystallization. Neutral forms of drugs are important for higher membrane permeability, while zwitterions are more soluble in water. The twin advantages of higher solubility/dissolution rate and good stability of neutral SPX are achieved in a molecular cocrystal compared to its zwitterionic SPX hydrate. The amine-phenol supra-molecular synthon drives cocrystal formation, with the paraben ester acting as a "proton migrator'' for the ionic to neutral transformation.

Polymorphism, isostructurality and physicochemical properties of glibenclamide salts - Suresh, Kuthuru; Khandavilli, U. B. Rao; Gunnam, Anilkumar; Nangia, Ashwini (CrystEngComm, 2017)
Novel salts of glibenclamide (GBA), namely glibenclamide-sodium (GBA-Na), glibenclamide-potassium (GBA-K) and glibenclamide-ammonium (GBA-NH4) were crystallized under different conditions to obtain their polymorphs, and their aqueous solubility and hydration stability studies are reported. The GBA-Na salt is dimorphic (forms I and II)and also exists as hydrate GBA-Na-H2O (form III). The GBA-K salt exists in anhydrous and hydrate forms (GBA-K, forms I and II). Crystal structure analysis of GBA-Na forms I and II showed differences in geometry of the central metal atom and ligand orientation. This kind of polymorphism of sulfonyl urea salts appears to be novel in the Cambridge Structural Database (CSD). The iso-structurality of GBA-Na form I with GBA-NH4 and GBA-K form I salts is discussed. The potassium salts of GBA exhibited higher solubility compared to pure GBA. Specifically GBA-K salt forms I and II showed higher solubility by 77 fold in the water and 33 fold in phosphate buffer (pH 7) compared to the other salts. Dynamic vapor sorption (DVS) showed reversible water sorption without hysteresis for all salts, except for GBA-K form II which transformed to form I after a sorption and desorption cycle as confirmed by PXRD.

Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Salts and salt cocrystals of the antibacterial drug pefloxacin - Gunnam, Anilkumar; Suresh, Kuthuru; Nangia, Ashwini (Crystal Growth & Design, 2018)
Pefloxacin (PEF) is an amphoteric, antibacterial drug which exists as a neutral molecule in the crystal structure stabilized by C-H center dot center dot center dot O and C-H center dot center dot center dot F interactions. The design of multicomponent solids using crystal engineering was undertaken in a cocrystal/salt screen of PEF with generally recognized as safe (GRAS) dicarboxylic acids to improve the solubility and phase stability of the drug. Ten multicomponent forms, namely, five salts, two salt hydrates, and three salt cocrystals, were prepared by liquid-assisted grinding followed by crystallization. In some cases, salt and salt cocrystals were obtained concomitantly during solution evaporative crystallization. Single crystal X-ray diffraction showed that the structures are stabilized by N+-H center dot center dot center dot O-, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot F, and pi-pi stacking interactions. The bulk phase purity of multicomponent forms was characterized by powder X-ray diffraction, spectroscopy, and thermal techniques. The salt/salt cocrystal forms exhibit a faster dissolution rate and higher solubility compared to pure PEF in pH 1.2 (acidic, like gastric environment) and pH 7 phosphate buffer media (neutral, like intestinal passage). Specifically the PEF+-SA(-) salt (SA = succinic acid) showed remarkably high solubility, dissolution rate, and stability compared to the other multicomponent forms and PEF neutral form. The drug formulation compatible pefloxacin succinate is a promising soluble and stable PEF salt.

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.

Hepatoprotective cocrystals of isoniazid: synthesis, solid state characterization, and hepatotoxicity studies - Yadav, Balvant; Gunnam, Anilkumar; Thipparaboina, Rajesh; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2019)
Isoniazid (INH) is one of the first line drugs used in combination with pyrazinamide and rifampicin for the management of tuberculosis. Idiosyncratic hepatotoxicity is one of the most common side effects of antitubercular therapy worldwide. The current study explores solid phase modification of INH by cocrystallization with various hepatoprotective coformers, namely chrysin, hesperetin, silibinin, syringic acid (SYRA), and quercetin (QUE) to address hepatotoxicity concerns. Cocrystals were obtained with SYRA and QUE. Supramolecular synthons based on pyridine-carboxyl and pyridine-hydroxyl synthon enabled the formation of cocrystals. INHSYRA and INHQUE cocrystals were characterized by FT-IR, DSC, and PXRD. Single crystal X-ray analysis of INHSYRA revealed that it crystallized in triclinic system with the P (1) over bar space group. Intrinsic dissolution rate studies (IDR) showed slow drug release from both the cocrystals. Hepatoprotective effects of INHSYRA and INHQUE cocrystals were evaluated by a single toxic dose study and a subchronic study for 28 days. Results from the subchronic study indicated significant increase in ALT, AST, and ALP enzyme levels in the INH-treated group whereas the enzyme levels in INHSYRA and INHQUE cocrystal treated group were comparable to that of the untreated group. This study demonstrates the in vivo hepatoprotective effects of coformers SYRA and QUE provide promising evidence for utility of nutraceutical based coformers, to tackle hepatotoxicity associated with various drugs.

High-solubility salts of the multiple sclerosis drug teriflunomide - Gunnam, Anilkumar; Nangia, Ashwini K. (Crystal Growth & Design, 2019)
Teriflunomide (TFM) is an immunomodulatory prodrug of leflunomide which is used for the treatment of multiple sclerosis (MS). It is a Biopharmaceutics Classification System Class (BCS) II drug with low solubility and high permeability. The X-ray crystal structure of TFM is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, and N-H center dot center dot center dot N interactions. In order to study the solubility and dissolution changes of this drug, five multicomponent crystal forms were prepared with amine and amide generally regarded as safe (GRAS) coformers to improve the physicochemical properties such as solubility, dissolution, diffusion, and phase stability. Equimolar TFM-coformer 1:1 salts were crystallized, except for cytosine which afforded a salt cocrystal toluene solvate TFM-CYT-TOL in a 1:2:1 ratio. The multicomponent forms were crystallized by slow solvent evaporation and characterized by single crystal X-ray diffraction. TFM and coformer are bonded by N+-H center dot center dot center dot O-, N-H center dot center dot center dot O, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, N-H center dot center dot center dot N, and C-H center dot center dot center dot F interactions. The bulk phase purity of the salts was characterized by powder X-ray diffraction and infrared and thermal techniques. Solubility, dissolution, and diffusion experiments in pH 7.0 buffer exhibited a significant improvement compared to the reference drug. The morphology and particle size of salts by field emission scanning electron microscopy were related to dissolution behavior. The highest solubility, dissolution, and diffusion profile were observed for TFM-MEA and TFM-TEA salts (monoethanol amine and triethanol amine).

Generation and evaluation of pharmacologically relevant drug-drug cocrystal for gout therapy - Modani, Sheela; Gunnam, Anilkumar; Yadav, Balvant; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2020)
The present study reports a novel drug-drug cocrystal of febuxostat and piroxicam for the treatment of gout. Single crystal X-ray diffraction revealed a monoclinic system with P2(1)/c space group. The prepared cocrystal enhanced the solubility of febuxostat and piroxicam and improved the dissolution rate of piroxicam in pH 6.8 as compared to the pure drug. Further, the compressibility assessment of cocrystal by Aulton and Wells method confirmed its plastic behavior and suitability for direct compression.

Improving the dissolution rate of the anticancer drug dabrafenib - Rai, Sunil K.; Gunnam, Anilkumar; Mannava, M. K. Chaitanya; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Dabrafenib (DBF) is an anticancer drug with selective B-Raf (BRAF) inhibition activity. In 2013, DBF was approved by the U.S. Food and Drug Administration (US-FDA) as a dabrafenib mesylate salt (DBF center dot MS). Because of insolubility in aqueous medium, specifically at the pH 4-8 biorelevant range, DBF is a Biopharmaceutics Classification System (BCS) Class II drug (i.e., low solubility and high permeability). Therefore, screening of novel salts and cocrystals was carried out using Generally Recognized as Safe (GRAS) coformers. A total of 10 salts/cocrystals including the mesylate salt were found to be stable under the crystallization conditions. Among acidic coformers, methane sulfonic acid (MS) and saccharin (SACH) formed salts, while fumaric acid (FA), succinic acid (SA), and adipic acid (ADA) gave cocrystals. However, monoamines formed a monohydrate salt where the water molecule is hydrogen bonded with the aminopyrimidine moiety of DBF. The replacement of monoamines with ethylenediamine (EN) dislocated the water molecule near the free amine of EN in the crystal structure with a change in space group from triclinic (P (1) over bar) to monoclinic (P2(1)/n). Dissolution measurements at pH 1.2 (0.1 N HCl) showed that DBF center dot EN superset of H2O dissolved rapidly compared to the DBF.MS salt (the dissolution rate of DBF center dot EN superset of H2O and DBF center dot MS is 11 and 2 times faster than that of DBF). Structure-activity relationship analysis showed that bonding of the aminopyrimidine moiety with strong hydrogen bond synthons inhibited dissolution, whereas a loosely bound or free site at the aminopyrimidine moiety enhanced the dissolution rate. Finally, a cytotoxicity study was performed for DBF, DBF center dot MS, and DBF center dot EN superset of H2O, which showed that DBF center dot EN superset of H2O is safe for normal cells and yet equally potent against cancer cells. Crystal engineering of an improved formulation of dabrafenib center dot ethylenediamine hydrate is presented as a new anticancer drug.

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.

Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.